1990
DOI: 10.1113/jphysiol.1990.sp018220
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of the cutaneomuscular reflex recorded from the first dorsal interosseous muscle in man.

Abstract: SUTMMARY1. Cutaneous reflexes have been recorded from the first dorsal interosseous muscle following electrical stimulation of the digital nerves of the index finger in man. Recordings have been obtained from 127 children, aged from 3 to 18 years while each performed an isometric abduction of the index finger and whole hand grips.2. In the adult, reflexes recorded while subjects performed an isometric abduction of the index finger consisted of three readily identifiable components within the first 100 ms. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…The latency of the following sharp burst, also triggered by the start of the slip, is in agreement with the long-latency excitatory response seen in cutaneomuscular reflex experiments (see the discussion above and (Evans et al 1990(Evans et al , 1991Issler and Stephens 1983;Jenner and Stephens 1982)). The response latencies (43 Ļ® 17 ms) for the burst in primary motor neurons in the monkey discussed in the preceding text (Bourdreau and Smith 2001;Picard and Smith 1992b) were similar to our data (44 Ļ® 18 ms).…”
Section: Model and Behavior Suggests Supraspinal Controlsupporting
confidence: 70%
“…The latency of the following sharp burst, also triggered by the start of the slip, is in agreement with the long-latency excitatory response seen in cutaneomuscular reflex experiments (see the discussion above and (Evans et al 1990(Evans et al , 1991Issler and Stephens 1983;Jenner and Stephens 1982)). The response latencies (43 Ļ® 17 ms) for the burst in primary motor neurons in the monkey discussed in the preceding text (Bourdreau and Smith 2001;Picard and Smith 1992b) were similar to our data (44 Ļ® 18 ms).…”
Section: Model and Behavior Suggests Supraspinal Controlsupporting
confidence: 70%
“…The latency difference for motor evoked potentials recorded from contracted or relaxed muscles following transcranial magnetic brain stimulation decreases until 10-12 years of age, and has been used as an indicator of the maturation of the corticospinal pathway (Caramia, Desiato, Cicinelli, Iani & Rossini, 1993). In young subjects, the E2 component of the cutaneomuscular reflex, which is thought to involve activity in a transcortical pathway that includes the corticospinal tract, increases in size until 14-15 years of age (Evans et al 1990 (Kirkwood & Sears, 1978, Vaughan & Kirkwood, 1993. The relative weighting of these factors is determined by the level of synaptic noise and the size of the EPSPs (Gustaffson & McCrea, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Many factors underlie this increase in manual dexterity including a change in the use of motor pathways, in particular of the corticospinal motor system. In their study of reflex motor development, for example, Evans, Harrison & Stephens (1990) found that transcortically mediated reflex responses elicited by exciting the digital nerves of the fingers were not present in intrinsic hand muscles of children aged less than 4 years. Such responses became progessively more prominent and attained adult values in most individuals by the early teenage years.…”
mentioning
confidence: 99%
“…From these observations, it was concluded that E1 has a spinal pathway; and E2 is of supraspinal origin requiring transmission of afferent impulses through the dorsal columns, a relay in the sensorimotor cortex, and descending transmission to the lower motoneuron pool by way of the corticospinal tract 12) . To date, cutaneous reflexes have been shown to be modulated in an age-, task-, and training-dependent manner 9,10,13) . Cutaneous reflexes can be elicited in leg (hindlimb in quadrupeds) muscles as well.…”
Section: Neurophysiological Bases Of Reflex Responses Arising From Cumentioning
confidence: 99%
“…Noxious reflexes are therefore thought to be indicative of a modular organization of the spinal cord to produce a seminal functional outcome during locomotion in response to noxious sensation 5) . Different from the noxious reflexes, cutaneous afferents arising from low threshold mechanoreceptors existing under the skin surface can give rise to widespread and segmental excitatory and suppressive reflex effects in various motoneuron pools (cutaneous reflexes for review, see [6][7][8] ) To date, the cutaneous reflexes in human hand muscles have been demonstrated to be modulated in a task-, ageand pathological-dependent manner [9][10][11][12][13] . Interestingly, the functionally relevant reflexes occur during human walking 14,15) .…”
Section: Introductionmentioning
confidence: 99%